Improving Distance Learning Security using Machine Learning - Ahmad, Asiyah (PT. Lentera Ilmu Publisher, 2023)
This study explores the intersection of machine learning and distance learning security, aiming to fortify online educational platforms amidst the evolving digital landscape. With technological advancements fueling the rise of distance learning, concerns regarding cybersecurity in virtual educational environments have grown significantly. The fusion of machine learning and distance learning security represents a proactive approach to bolstering safety and integrity within virtual classrooms. Leveraging sophisticated algorithms, this amalgamation seeks to preempt security breaches by identifying irregular patterns, addressing vulnerabilities, and swiftly countering risks like phishing attempts and data breaches. By utilizing historical data and real-time monitoring, machine learning models offer predictive capabilities, enabling educational institutions to anticipate emerging threats and safeguard the learning process while ensuring data integrity and user privacy. While machine learning techniques, such as anomaly detection and predictive modeling, have shown promise in fortifying security measures, ethical considerations and collaborative efforts are essential for responsible implementation. This comprehensive study, involving literature review, knowledge enrichment, case studies, and informed conclusions, aims to guide further research and practical applications in enhancing distance learning security through machine learning.